Strategic Ambidexterity in Maritime Enterprises: Balancing Operational Efficiency and Sustainability Innovation in the Context of IMO 2050 Decarbonization Targets - Meilinasari Nurhasanah Hutagaol; Ardiansyah; Muhammad Nurdin; Sursina; Marudut Bernadtua Simanjuntak (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The IMO 2050 decarbonization strategy presents global shipping enterprises with a defining strategic paradox: the need to simultaneously maximize operational efficiency from existing conventional fleet assets while investing in the exploration of transformative sustainability innovations — a challenge that resonates profoundly with the strategic management concept of organizational ambidexterity. This study examines how global maritime enterprises manage the tension between exploitation of existing capabilities and exploration of new sustainability competencies in pursuit of IMO 2050 targets. Employing a qualitative research design grounded in thematic analysis, the study engages thirty senior executives and strategic management professionals from leading global shipping companies, maritime investment firms, and international regulatory organizations. Findings reveal three distinct ambidexterity configurations — structural, contextual, and temporal — and identify five organizational enabling conditions that distinguish successfully ambidextrous maritime enterprises from those caught in strategic trade-off paralysis. The study contributes to both strategic management theory and maritime management scholarship by advancing the application of ambidexterity concepts in capital-intensive, heavily regulated global industries.